Consumption of cranberry and probiotics as a natural remedy for urinary tract infections - Orłowska, Dominika; Zalewa, Karolina; Olszak, Joanna; Bartoszek, Lidia; Kapłan, Wojciech (Quality in Sport, 2024)
Introduction and Purpose Urinary tract infections (UTIs) are a prevalent health issue caused primarily by uropathogenic Escherichia coli (UPEC) and other pathogens, affecting millions annually. These infections encompass lower (cystitis) and upper (pyelonephritis) tract manifestations, presenting with symptoms ranging from dysuria to severe complications like sepsis. Traditional antibiotic treatments, while effective, are increasingly challenged by resistance and adverse effects, necessitating exploration of alternative therapies. Cranberry-derived compounds, particularly proanthocyanidins (PACs), are known for their ability to inhibit bacterial adhesion to uroepithelial cells, a critical step in UTI pathogenesis. Clinical studies suggest that cranberry products may reduce UTI incidence, especially in vulnerable populations such as women and catheterized patients. Probiotics, specifically lactobacilli, contribute to urogenital health by competing with uropathogens for epithelial cell binding sites and producing antimicrobial substances. Emerging research highlights the potential synergistic benefits of combining cranberry extracts with probiotics in UTI prevention strategies. Material and Methods This review is based on articles from the PubMed database, covering the years 2004-2023, using keywords: urinary tract infections, cranberry, probiotics, E. Coli, antibiotics Conclusions Cranberry products and probiotics offer promising non-antibiotic approaches for UTI prevention, targeting fundamental aspects of bacterial pathogenesis. While preliminary studies indicate promising outcomes, rigorous clinical trials are essential to validate these combinations and optimize therapeutic protocols. Further research is warranted to identify specific bioactive compounds within cranberries, standardize probiotic formulations, and establish comprehensive guidelines for their clinical use in UTI management.